Pengembangan Media Game Edukasi Geopoly Nusantara Sebagai Penguatan Pemahaman Geokultural Siswa SMP Negeri 34 Surabaya - Lailatul Chusnunisa; Riyadi R; Ali Imron; Durrotun Nafisah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aimed to develop the Geopoly Nusantara Educational Game as a learning medium that is valid, practical, and effective in strengthening students' geocultural understanding in Social Studies learning for eighth-grade students at SMP Negeri 34 Surabaya. This research employed a Research and Development (RD) method using the ADDIE development model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The research instruments included material expert validation sheets, media expert validation sheets, teacher practicality questionnaires, student response questionnaires, and geocultural understanding tests. Data were analyzed using descriptive quantitative analysis for validation and questionnaire results, while the effectiveness of the learning media was examined through normality tests, homogeneity tests, and the Independent Samples t-test. The findings revealed that the Geopoly Nusantara Educational Game achieved the very feasible category based on evaluations from both material and media experts. The teacher practicality assessment and student responses also indicated that the learning media was very practical, demonstrating its ease of use in classroom learning. Furthermore, the effectiveness test showed a significant difference between the experimental and control groups after the implementation of the learning media, indicating that the Geopoly Nusantara Educational Game effectively strengthened students' geocultural understanding. Therefore, the developed learning media can serve as an interactive and engaging alternative for Social Studies instruction while enhancing students' understanding of the relationship between geographical conditions and Indonesia's cultural diversity.